2018
DOI: 10.1111/jsr.12722
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders, depression and anxiety are associated with adverse safety outcomes in healthcare workers: A prospective cohort study

Abstract: The objective of the study was to determine if sleep disorder, depression or anxiety screening status was associated with safety outcomes in a diverse population of hospital workers. A sample of shift workers at four hospitals participated in a prospective cohort study. Participants were screened for five sleep disorders, depression and anxiety at baseline, then completed prospective monthly surveys for the next 6 months to capture motor vehicle crashes, near-miss crashes, occupational exposures and medical er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 43 publications
1
102
1
8
Order By: Relevance
“…The increased risk of infection and stressful environment might have contributed to higher mental health impacts among health workers in China than in Nepal [ 5 , 8 , 31 ]. Mental health outcomes among health workers affect their work performance and to address this, specialised mental health services are required [ 8 , 32 , 33 ]. The higher perceived risk and having to stay in quarantine during the epidemic might not just result in short term impacts but also lead to long term mental health consequences among health workers [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of infection and stressful environment might have contributed to higher mental health impacts among health workers in China than in Nepal [ 5 , 8 , 31 ]. Mental health outcomes among health workers affect their work performance and to address this, specialised mental health services are required [ 8 , 32 , 33 ]. The higher perceived risk and having to stay in quarantine during the epidemic might not just result in short term impacts but also lead to long term mental health consequences among health workers [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of infection and stressful environment might have contributed to higher mental health impacts among health workers in China than in Nepal [5,8,31]. Mental health outcomes among health workers affect their work performance and to address this, specialised mental health services are required [8,32,33]. The higher perceived risk and having to stay in quarantine during the epidemic might not just result in short term impacts but also lead to long term mental health consequences among health workers [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mental health problems are an important cause of workplace illness (Roelen et al, ). Studies have shown that nurses' mental health problems impact the amount of sick leave taken, the willingness to leave and patient safety (Hilton, Scuffham, Sheridan, Cleary, & Whiteford, ; Weaver et al, ). Patient safety comprises an important part of management responsibilities (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Work engagement mediated the relationship between job characteristics and intention to leave the profession (Wan, Li, Zhou, & Shang, ). Moreover, health care workers' depression and anxiety were linked to poor patient safety outcomes (Weaver et al, ). Thus, we form the following hypotheses:…”
Section: Introductionmentioning
confidence: 99%